The Influence of the Singing Method on the Ability to Recognize Letters for Children in Group B of Pelangi Kindergarten, Medan Tembung District - Nelly Masnaria Purba; Sariana Marbun (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the results of the ability to recognize letters through the singing method in group B Pelangi Kindergarten children, Medan Tembung District. To find out the effect of singing methods on the ability to recognize letters in group B TK Pelangi. The research method used is quasi-experimental. The sample of this study were 20 children taken from 2 classes with a total of 43 children. Instrument testing was carried out with a test in the form of a statement of 15 statements. The data analysis technique used is a non-parametric analysis technique with the Wilcoxon test. The results of this study were that the average value given the treatment of the ability to recognize children's letters was 13.5 in the very good category, while not being treated with the ability to recognize children's letters was 11.3 in the good category. From the score data shows that learning activities using the singing method can improve the ability to recognize letters in group B TK Pelangi Medan